2013
DOI: 10.1021/jp400607s
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Gold Nanorods for High-Temperature Plasmonic Sensing

Abstract: There are many potential sensing applications for Au nanorods due to a tunable localized surface plasmon resonance (LSPR) frequency that changes with aspect ratio. However, their application at high temperatures is limited due to a shape change that can take place well below the melting point of bulk Au, driven by a reduction in surface energy. A method of stabilizing Au nanorods is provided here by encapsulating them with a 15 nm capping layer of yttria stabilized zirconia (YSZ). After annealing rods with nom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 40 publications
0
54
0
Order By: Relevance
“…The plasmonic properties of gold nanorods allow them to be used in photothermal therapy [1,2], imaging techniques [3,4], theranostics [5,6], sensing applications [7][8][9][10] and optical memories [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasmonic properties of gold nanorods allow them to be used in photothermal therapy [1,2], imaging techniques [3,4], theranostics [5,6], sensing applications [7][8][9][10] and optical memories [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…in photothermal therapy [1,2] and photoacoustic imaging [36][37][38]. It was shown that embedding the nanorods into a titaniumoxide matrix [39], or coating with carbon [40] or other materials [7,25] can protect them from shape transformations during heating up to ~690 °C. For silica shells, however, the temperature related shape change of the core/shell nanoparticles upon bulk heating was investigated only up to 260 °C and for aspect ratios higher than 4 [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5 shows results for a metal backed thin absorbing layer, where the carbon is placed on 200nm of gold. This metal can be used to around 500K [26], [27] and will allow initial room temperature and medium temperature studies to be performed in future. Later in the paper we show results using the high melting point metal tungsten.…”
Section: Resultsmentioning
confidence: 99%
“…The State University of New York (SUNY; DE-FE0007190) is developing heat-activated plasmonic chemical sensors for H 2 , CO, and NO 2 capable of 500 -800°C operation [22]. The technology is centered on creating gold (Au) nanoparticles embedded in a metal oxide matrix with stabilized geometry and optical signature at high temperatures [22,23]. The University of Pittsburgh (#DE-FE0003859) have conducted research in fiber optic sensor platform technology that is stable up to 1100°C and capable of measuring optical flow, temperature (up to 800°C), pressure (15 -2000psi), and H 2 concentration (0.2 -10%) [24].…”
Section: Extramural Research Program Overviewmentioning
confidence: 99%